Challenges in Implementing the Merdeka Curriculum in Junior High Schools: A Systematic Literature Review - Mardiatun Nissa; Velina Cindy Sagita (PT. Intelek Cendikiawan Nusantara, 2025)
The Merdeka Curriculum is implemented to meet the demands of 21st-century learning through flexibility, simplification of material, and strengthening of the Pancasila Student Profile. This study aims to identify the challenges of implementing the Merdeka Curriculum at the junior high school level through a Systematic Literature Review (SLR) approach. Articles were searched for through Mendeley, ScienceDirect, and Google Scholar using the PRISMA guidelines, with criteria of articles published between 2020 and 2025, written in English, and discussing implementation challenges in junior high schools. A total of 16 articles met the inclusion criteria. The results show that this curriculum offers positive opportunities, such as increased teacher creativity and more contextual learning, but implementation challenges remain dominant. The main obstacles include low teacher understanding of core concepts such as differentiation, formative assessment, and teaching module development, limited school facilities and technology, low student motivation and readiness, and a lack of training and ongoing mentoring. In addition, the transition from the previous curriculum and lack of parental support also hindered the implementation process. These findings emphasize that the success of the Merdeka Curriculum requires increased teacher capacity, improved infrastructure, and systematic and continuous support.